Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1080/01457630701758039
|View full text |Cite
|
Sign up to set email alerts
|

An Inverse Problem Method for Overall Heat Transfer Coefficient Estimation in a Partially Filled Rotating Cylinder

Abstract: The objective of this article is to study the estimation of an overall heat transfer coefficient in a partially filled rotating cylinder. Herein is an inverse analysis for estimating the overall heat transfer coefficient in an arbitrary cross-section of the aforementioned system from the temperatures measured on the shell. The material employs the finite-volume method to solve the direct problem. The hybrid effective algorithm applied here contains the local optimization algorithm to estimate the unknown param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…They found that the convective heat transfer coefficient varied from 1.31 to 12.7 W/m 2 -• C for different crops with an experimental error up to 20%. A method was introduced for estimating the overall heat transfer coefficient in the partially filled rotating cylinder by Farhaneih and Heydari [6]. Temperature reading on the surface of the rotating cylinder was taken and the overall heat transfer coefficient was estimated using inverse heat transfer techniques.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the convective heat transfer coefficient varied from 1.31 to 12.7 W/m 2 -• C for different crops with an experimental error up to 20%. A method was introduced for estimating the overall heat transfer coefficient in the partially filled rotating cylinder by Farhaneih and Heydari [6]. Temperature reading on the surface of the rotating cylinder was taken and the overall heat transfer coefficient was estimated using inverse heat transfer techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of measuring directly, an alternative method is investigated by solving an inverse two-dimensional non-linear heat conduction problem. Several methods have been proposed in the literature to solve such inverse problem as presented in [13] with primary examples for the estimation of heat transfer coefficients in [14,15]. Here, the Bayesian framework statistics is selected for estimating the model parameters [16,17].…”
Section: Introductionmentioning
confidence: 99%